On-chip ultra-fast data acquisition system for optical scanning acoustic microscopy using 0.35um CMOS technology - Dong, Peiliang (2009)
Optical Scanning Acoustic Microscopy (OSAM) is a non-contacting method of investigating the properties and hidden faults of solid materials. This thesis presents an ultra-fast data acquisition system (DAQ) which samples and digitises the output signal of OSAM. The author's work includes the design of the clock source and the sampler, and integration of the whole system.